THE IMPACT OF BIOTECHNOLOGY PRODUCT INNOVATION AND CORPORATE STRATEGY IN MEDIUM-SCALE SEAWEED INDUSTRY COMPANIES ON THE COMPANY BUSINESS GROWTH (CASE STUDY: OCEAN FRESH CV) - Sultan Eka Buana, Archie
Biotechnology is a developmental process of product innovation that can provide many benefits to the environment and consumers. One resource that has great potential is derived from the sea, namely seaweed. The utilization of Seaweed product innovation using a biotechnology approach can be a new prospect for various industries in the future. So far, what has been developing in the marine industry in general, seaweed products have not been utilized optimally. The progress of product innovation in this industry also encourages the blue economy concept. This study will examine how the seaweed biotechnology product innovation development is carried out which aims as a case study to see the impact resulting from the company's product innovation and corporate strategy in this industry. This research will be conducted at a mid-level company whose business focus is on biotechnology products from seaweed and who has become the leader in the market in promoting the development of biotechnology innovation in its products, namely Ocean Fresh CV. The study was conducted by looking at the impact resulting from the rate of product innovation in the company and how the resulting impact on the company's business growth. High innovation, both process innovation, and product innovation will increase the company's ability to create quality products. This research was carried out qualitatively descriptively using semi-structured interviews and questionnaires to survey customers on a non-probability basis, namely convenience random sampling. Data analysis will be carried out using a qualitative descriptive approach and visualized with descriptive modeling by analyzing using internal and external evaluation approaches and then summarized using Balanced Scorecard analysis to see the ideal strategy for this company going forward. Then after that, a scenario planning matrix will be carried out based on existing data to be able to project in the future how the impact that has been assessed from the results of product innovation can have a positive effect on the company's future business growth. So that it can be concluded in the end regarding the research on the impact of the rate of product innovation development and corporate strategy on business growth in the company Ocean Fresh CV. This study concluded that the impact of the product innovation development carried out so far has had a very positive impact on the company's business growth. Common problems were also found as well as surveys from a customer perspective which could also be useful for future improvements and are expected to be useful for similar business players in this industry in Indonesia to be able to improve the national economy from the marine biotechnology sector. Recommendations and suggestions in this study are Ocean Fresh can use several scenarios that have been prepared in this study to be able to choose an appropriate strategy to increase business growth for the company and that it is necessary to carry out further research that discusses this industry in a comprehensive and macro manner and to take examples from other companies as a comparison from this research. It is also hoped that there will be future similar research that can produce a better business implementation so that it can provide great benefits for the growth of the marine biotechnology industry in Indonesia. It is also necessary to compare how this industry moves in other countries for future research.